2001
DOI: 10.1002/jps.1112
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a Solvent System for Spherical Crystallization of Salbutamol Sulfate by Quasi‐Emulsion Solvent Diffusion (QESD) Method

Abstract: In this paper we describe how the spherical crystallization process by QESD method can be applied to a water-soluble drug, salbutamol sulfate. The type of solvent, antisolvent, and emulsifier and the concentration of emulsifier to be used for the production of spherical particles with a size range 80-500 microm are determined. Furthermore, the solvent/antisolvent ratio and the temperature difference between them (Delta T) are studied. It was observed that, in the case of salbutamol sulfate, the Delta T value h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 8 publications
1
46
0
Order By: Relevance
“…To sample the dissolution medium, a standard dissolution vessel was equipped with a medium recirculation system. The dissolution medium was constantly circulated using a LSMatec peristaltic pump fitted with a 0.45‐μm filter, through a 2 mm flow‐through UV cuvette placed in a Cecil CE2020 UV‐spectrophotometer set to 276 nm 28. The rate of medium circulation was set to 25 mL/min, and the pH of the aqueous medium was monitored using a Thermo Orion 420+ pH meter.…”
Section: Methodsmentioning
confidence: 99%
“…To sample the dissolution medium, a standard dissolution vessel was equipped with a medium recirculation system. The dissolution medium was constantly circulated using a LSMatec peristaltic pump fitted with a 0.45‐μm filter, through a 2 mm flow‐through UV cuvette placed in a Cecil CE2020 UV‐spectrophotometer set to 276 nm 28. The rate of medium circulation was set to 25 mL/min, and the pH of the aqueous medium was monitored using a Thermo Orion 420+ pH meter.…”
Section: Methodsmentioning
confidence: 99%
“…As previous studies have shown, solvent transfer is particularly influenced by two basic parameters (38,40). One of them is the difference in temperatures T 1 -T 2 , with T 1 being the temperature of the good solvent with dissolved drug before dispersion and T 2 the initial temperature of the poor solvent.…”
Section: Quasi-emulsion Solvent Diffusionmentioning
confidence: 99%
“…Only the use of the most lipophilic emulsifier in the study, Abil EM 90 (polysiloxane poly alkyl polyether copolymer; HLB = 5), yielded spherical particles. A larger amount of emulsifiers dispersed in the poor solvent can cause a coalescence of particles and increase their surface roughness, whereas a lower proportion of emulsifier increases the apparent density of particles (40). In a study by Zhang and coworkers, a trial without surfactant resulted in relatively large spherical particles of silybin (6.68 mm) with coarse surfaces, and trials with lower or higher concentrations of surfactant yielded smaller particles (2.97 mm, 2.49 mm, and 2.48 mm at 0.01, 0.02, and 0.10 % SDS concentration, respectively) with narrower particle size distribution (42).…”
Section: Quasi-emulsion Solvent Diffusionmentioning
confidence: 99%
“…The vials were shaken for two hours on mechanical shaker (Nocent et al, 2001). The solution was filtered and analysed for drug content spectrophotometrically at 234 nm.…”
Section: Solubility Studiesmentioning
confidence: 99%